Neuroprotective effects of antibodies on retinal ganglion cells in an adolescent retina organ culture. (16th September 2016) - Bell, Katharina; Wilding, Corina; Funke, Sebastian; Perumal, Natarajan; Beck, Sabine; Wolters, Dominik; Holz‐Müller, Jana; Pfeiffer, Norbert; Grus, Franz H.
Abstract : Loss of retinal ganglion cells (rgc) in glaucoma leads to blindness. Several antibodies are down‐regulated in glaucoma patients. Our aim was to test if these antibodies have a protective effect of rgc in a retinal organ culture. This could be shown with an increase of rgc numbers. This effect results through reduced stress levels and the shift of glutamine synthetase localization. Abstract: Glaucoma, a neurodegenerative disease, is characterized by a progressive loss of retinal ganglion cells (rgc). Up‐ and down‐regulated autoantibody immunoreactivities in glaucoma patients have been demonstrated. Previous studies showed protective effects of down‐regulated antibodies [gamma (γ)‐synuclein and glial fibrillary acidic protein [GFAP]) on neuroretinal cells. The aim of this study was to test these protective antibody effects on rgc in an organ culture model and to get a better understanding of cell–cell interactions of the retina in the context of the protective effect. We used an adolescent retinal organ culture (pig) with an incubation time of up to 4 days. Retinal explants were incubated with different antibodies for 24 h (anti‐GFAP, anti‐γ‐synuclein and anti‐myoglobin antibody as a control). Brn3a and TUNEL staining were performed. We also conducted glutamine synthetase staining and quantification of the retinal explants. Mass spectrometry analyses were performed as well as protein analyses via microarray. We detected a continuous decrease of rgc/mm in the retinal explants throughout the 4 days of incubation with increased TUNEL rgc staining. Immunohistochemical analyses showed a protective effect of anti‐γ‐synuclein (increased rgc/mm of 41%) and anti‐GFAP antibodies (increased rgc/mm of 37%). Mass spectrometric, microarray and immunohistochemical analyses demonstrated Müller cell involvement and decreased endoplasmic reticulum stress response in the antibody‐treated retinae. We could detect that the tested antibodies have a protective effect on rgc which seems to be the result of reduced stress levels in the retina as well as a shift of glutamine synthetase localization in the endfeet of the Müller cells towards the inner retinal layer. Loss of retinal ganglion cells (rgc) in glaucoma leads to blindness. Several antibodies are down‐regulated in glaucoma patients. Our aim was to test if these antibodies have a protective effect of rgc in a retinal organ culture. This could be shown with an increase of rgc numbers. This effect results through reduced stress levels and the shift of glutamine synthetase localization.